Red clover increases micronutrient concentrations in forage mixtures - Lindström, Bodil E.M.; Frankow-Lindberg, Bodil E.; Dahlin, A. Sigrun; Watson, Christine A.; Wivstad, Maria (Field crops research, 2014)
•Four grass–clover–chicory mixtures were grown on three contrasting sites.•Chicory and clovers had higher micronutrient concentrations than grasses.•Mixture micronutrient concentrations increased with red clover proportion.•Site properties affected overall micronutrient levels in species and mixtures. Forage crops provide micronutrients as well as energy, protein and fibre to ruminants. However, the micronutrient concentrations of forage plant species differ, legumes generally having higher concentrations than grasses. In addition to that there are also strong effects of soil type. Typically, the concentrations of one or several micronutrients in forage are too low to meet the nutritional requirement of dairy cows. We hypothesized that the overall micronutrient (Co, Cu, Fe, Mn, Mo, Zn) concentrations of forage mixtures are affected by the red clover dry matter (DM) proportion and site effects. This hypothesis was tested at three contrasting sites. The results showed that increased red clover proportion increased the overall concentrations of several micronutrients in the mixtures at all sites. At the site with the widest range of red clover proportion (0–70%) in the mixture, the Co, Cu and Fe concentrations more than doubled between the lowest and highest red clover DM proportion. At the other two sites a smaller increase in red clover proportion (from 10% to 25% or from 25% to 50%) also increased the overall concentrations of Co by up to 80% but less for other micronutrients. One of the sites generally had higher micronutrient concentrations in the crop and removed larger amounts of micronutrients with the harvested biomass compared to the other two sites. This could be explained by differences in pH and micronutrient concentrations of the soils at the sites. We conclude that increased red clover proportion in the sward has the potential to increase the overall micronutrient concentrations but that the effect of the soil is also a controlling factor.